Bio-Inoculation of Tomato (Solanum lycopersicum L.) and Jalapeño Pepper (Capsicum annuum L.) with Enterobacter sp. DBA51 Increases Growth and Yields under Open-Field Conditions - John Paul Délano-Frier; Alberto Flores-Olivas; José Humberto Valenzuela-Soto (Agronomy, 2024)
The rhizobacterium Enterobacter sp. DBA51 (DBA51), isolated from the semi-desert in Coahuila, Mexico, was previously found to increase the vegetative growth of tomato and tobacco plants cultivated under greenhouse conditions. The present report describes the results obtained from two independent open-field experiments performed with tomato and jalapeño pepper commercial crops inoculated with DBA51. Additionally, plants inoculated with Bacillus subtilis LPM1 (LPM1) and uninoculated plants were included as positive and negative controls, respectively. DBA51 and LPM1 significantly promoted growth at vegetative stages in the tomato plants; this effect was evident in the stem diameter (DBA51 with p < 0.0001 and LPM1 with p < 0.0001) and height (DBA51 with p < 0.0001 and LPM1 with p < 0.0001) of the tomato plants. However, no differences were detected in the jalapeño pepper plants. Additionally, DBA51 and LPM1 treatments increased tomato fruit production by 80% and 31%, respectively, compared to uninoculated plants. A similar increase in yield was recorded in DBA51- and LPM1-treated jalapeño pepper plants, which was 75% and 56% higher than uninoculated controls, respectively. These results strongly recommend the potential use of DBA51 as a biofertilizer in horticultural crops.